Triphenylphosphine Derivatives of Allylbenzenes Express Antitumor and Adjuvant Activity When Solubilized with Cyclodextrin-Based Formulations - Igor D. Zlotnikov; Sergey S. Krylov; Marina N. Semenova; Victor V. Semenov; Elena V. Kudryashova (MDPI AG, 2023)
Allylbenzenes (apiol, dillapiol, myristicin and allyltetramethoxybenzene) are individual components of plant essential oils that demonstrate antitumor activity and can enhance the antitumor activity of cytotoxic drugs, such as paclitaxel, doxorubicin, cisplatin, etc. Triphenylphosphine (PPh3) derivatives of allylbenzenes are two to three orders of magnitude more potent than original allylbenzenes in terms of IC50. The inhibition of efflux pumps has been reported for allylbenzenes, and the PPh3 moiety is deemed to be responsible for preferential mitochondrial accumulation and the depolarization of mitochondrial membranes. However, due to poor solubility, the practical use of these substances has never been an option. Here, we show that this problem can be solved by using a complex formation with cyclodextrin (CD-based molecular containers) and polyanionic heparin, stabilizing the positive charge of the PPh3 cation. Such containers can solubilize both allylbenzenes and their PPh3 derivatives up to 0.4 mM concentration. Furthermore, we have observed that solubilized PPh3 derivatives indeed work as adjuvants, increasing the antitumor activity of paclitaxel against adenocarcinomic human alveolar basal epithelial cells (A549) by an order of magnitude (in terms of IC50) in addition to being quite powerful cytostatics themselves (IC50 in the range 1-10 µM). Even more importantly, CD-solubilized PPh3 derivatives show pronounced selectivity, being highly toxic for the A549 tumor cell line and minimally toxic for HEK293T non-tumor cells, red blood cells and sea urchin embryos. Indeed, in many cancers, the mitochondrial membrane is more prone to depolarization compared to normal cells, which probably explains the observed selectivity of our compounds, since PPh3 derivatives are known to act as mitochondria-targeting agents. According to the MTT test, 100 µM solution of PPh3 derivatives of allylbenzenes causes the death of up to 85% of A549 cancer cells, while for HEK293T non-cancer cells, only 15-20% of the cells died. The hemolytic index of the studied substances did not exceed 1%, and the thrombogenicity index was < 1.5%. Thus, this study outlines the experimental foundation for developing combined cytostatic medications, where effectiveness and selectivity are achieved through decreased concentration of the primary ingredient and the inclusion of adjuvants, which are safe or practically harmless substances.